A comparison of supraglottic airway i-gel™ vs. classic laryngeal mask airway in small children - Lee, Ju-Hyun (The Korean Society of Anesthesiologists, 2014)
BACKGROUND: i-gel™ is a new single-use supraglottic airway device without an inflatable cuff. This study was designed to compare the usefulness of i-gel™ versus a classic laryngeal mask airway (cLMA) in small children. METHODS: Sixty-three children (age range : 4-72 months) were randomly assigned to an i-gel™ or cLMA group. We evaluated hemodynamic data, airway sealing ability, the success rate of insertion, and adverse events including an inadvertent sliding out during ventilation. RESULTS: Demographic data and hemodynamic data obtained immediately after the insertion of these devices did not differ between the two groups. The success rates for insertion on the first attempt were 77 and 84% for i-gel™ and cLMA, respectively (P = 0.54), and the overall success rates were 87 and 100% respectively (P = 0.14). There were no significant differences in terms of airway leak pressure. The inserted i-gel™ inadvertently slid out in 8 of 31 patients but only one sliding out case occurred in the cLMA group (P = 0.02). There were no differences between the groups in terms of other side effects (e.g., coughing, bleeding) associated with the use of i-gel™ and cLMA (P = 0.75 and 0.49, respectively). CONCLUSIONS: Oropharyngeal leak pressure and insertion success rate of i-gel™ are similar to those of cLMA. However, i-gel™ is prone to inadvertent sliding out of the mouth in small children. Therefore, it is recommended that the i-gel™ should be secured more tightly to avoid displacement of the device.